2021
DOI: 10.1021/acsapm.1c00813
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Well-Compatibilized PP/PC Blends and Foams Thereof

Abstract: The performance of polypropylene-poly(ethylene brassylate) block and graft copolymers and a polypropylenepolycaprolactone graft copolymer as compatibilizers for polypropylene-rich polypropylene/bisphenol A polycarbonate (PP/PC, 80/ 20 wt/wt) blends was elucidated. The copolymers were synthesized either by metal-catalyzed ring-opening polymerization or transesterification of a presynthesized polyester, initiated by hydroxyl-functionalized PPs, which themselves were obtained by catalytic routes or reactive extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The affinity of the iPP-g-PCL copolymers for the blend components was also evidenced by changes in their thermal and rheological properties. 3,47 The significant decrease in iPP melting points in the compatibilized iPP/PC blends by 5−7 °C and the increase in iPP crystallization temperature within 4−10 °C were attributed to the presence of the iPP-g-PCL copolymer, acting as a heterogeneous nucleating agent.…”
Section: Polypropylene−bisphenol a Polycarbonate Blendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The affinity of the iPP-g-PCL copolymers for the blend components was also evidenced by changes in their thermal and rheological properties. 3,47 The significant decrease in iPP melting points in the compatibilized iPP/PC blends by 5−7 °C and the increase in iPP crystallization temperature within 4−10 °C were attributed to the presence of the iPP-g-PCL copolymer, acting as a heterogeneous nucleating agent.…”
Section: Polypropylene−bisphenol a Polycarbonate Blendsmentioning
confidence: 99%
“…To prepare iPP-based nanoporous membranes, we started form randomly OH-functionalized iPP prepared as described above, which can easily be converted into their corresponding amphiphilic graft copolymers via transesterification of pre-synthesized polyesters or catalytic ring-opening polymerization (cROP) of lactones. , For this study, the graft copolymers were synthesized via cROP of ε-caprolactone and δ-valerolactone initiated by poly­(propylene- co -10-undecen-1-ol) with a propylene volume fraction of 30 to 50%. , This composition range was considered to be the most promising to achieve interconnected two-phase nanostructure morphologies, which are necessary for membrane preparation. As proven by atomic force microscopy (AFM) analysis, the iPP- g -PVL and iPP- g -PCL copolymers with a polypropylene volume fraction of 33–36% and equal to 46% afforded interconnected two-phase morphologies and the iPP- g -PVL, containing 39% iPP, exhibited a periodic lamellar structure (Figure a).…”
Section: Pp-based Copolymers As Nanoporous Membrane Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, it's still a challenge to effectively prepare high-performance PC/PP alloys with approximate content. 12,13 In this work, a self-made compatibilizer was prepared by melt grafting reaction in the twin screw extruder, and three commercial compatibilizers were selected to systematically study effects of the compatibilizer type and content on the microstructure, mechanical properties, dielectric properties, and dynamic thermomechanical properties of PP/PC alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Lireza Azizi et al 11 prepared PP/PC/SEBS alloys with different SEBS contents by the melt‐blending method, and it was found that the size and quantity of core‐shell particles of PP/PC/SEBS alloys increased with the increase of SEBS content. So far, it's still a challenge to effectively prepare high‐performance PC/PP alloys with approximate content 12,13 …”
Section: Introductionmentioning
confidence: 99%